Regulating Autonomous Vessels : International, Regional, and European Regulation of Maritime Autonomous Surface Ships - Lange, Eva Ricard (International Law E-Books Online, Collection 2025, 2025)
This book adds to the legal research on autonomous vessels and proposes a combined international-supranational regulation concept, introducing the reader to the most urgent international legal aspects with respect to autonomous ships. The future legal framework must be technology-neutral and reliable, and it has to be in place as soon as possible to integrate autonomous ships into the existing international legal framework. The book provides the reader with a comprehensive and innovative comparison of different regulatory approaches, including regional and European instruments. The effect of non-binding instruments is analyzed based on rational choice theory.